The U.S. Military Veteran in News Photographs: Representation and Stereotypes. Issue 2 (3rd April 2019) - Parrott, Scott; Albright, David L.; Steele, Hailey Grace; Dyche, Caitlin
Abstract : Commenters have expressed concern over media content related to military veterans, saying journalists fail to provide the public with an accurate understanding of what it means to be a veteran. Nevertheless, few studies have examined the representation of veterans in news media content. The present study analyzed 740 photographs shared by regional news outlets on the popular social media platform Twitter. Coders documented the representation of veteran groups (gender, race, and service period) and stereotypes concerning veterans (homelessness, charity, and trauma) in the images. Results showed that the photographs rarely communicated stereotypes about veterans. Photographs overrepresented female veterans, although male veterans remained the significant majority. Minority veterans were underrepresented. Photographs most often contained images associated with World War II.